2014
DOI: 10.1186/1475-2875-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine efficacy studies confirm drug susceptibility of Plasmodium vivax in Chennai, India

Abstract: BackgroundAssessing the Plasmodium vivax burden in India is complicated by the potential threat of an emerging chloroquine (CQ) resistant parasite population from neighbouring countries in Southeast Asia. Chennai, the capital of Tamil Nadu and an urban setting for P. vivax in southern India, was selected as a sentinel site for investigating CQ efficacy and sensitivity in vivax malaria.MethodsCQ efficacy was evaluated with a 28-day in vivo therapeutic study, while CQ sensitivity was measured with an in vitro dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…Furthermore, similar therapeutic efficacy until day 28 has also been reported from other parts of India viz. 100% (41/41) from Mangalore [ 11 ], 98.1% (105/107) from Chennai [ 12 ] and 96.9% (63/65) from Gujarat [ 13 ] for CQ only and 100% (103/103) from Kolkata [ 14 ] for CQ–PQ combined regimen during the years 2003–2012. Notably, CQ–PQ combined regimen is known to have superior efficacy than CQ alone for preventing P. vivax recurrences [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similar therapeutic efficacy until day 28 has also been reported from other parts of India viz. 100% (41/41) from Mangalore [ 11 ], 98.1% (105/107) from Chennai [ 12 ] and 96.9% (63/65) from Gujarat [ 13 ] for CQ only and 100% (103/103) from Kolkata [ 14 ] for CQ–PQ combined regimen during the years 2003–2012. Notably, CQ–PQ combined regimen is known to have superior efficacy than CQ alone for preventing P. vivax recurrences [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clear association between the clinical outcome following a three-day CQ treatment and non-synonymous mutations in this gene has never been demonstrated elsewhere. In fact, the single 976 F mutant was not very common worldwide (7.4 %) [ 22 ], and the F F double mutant genotype was detected only in endemic regions of three countries: Brazil [ 36 , 37 ], Honduras [ 38 ] and Papua New Guinea [ 39 ]. In the samples herein analysed, no significant difference was observed between the presence of double 976 F /1076 L mutant (12 %) and single 976 F mutant (15 %) and no single 1076 L mutant was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in Thailand, Indonesia [ 17 ] and Myanmar [ 18 ], as well as in Mauritania [ 19 ] and Cambodia [ 20 ], it has been shown that 976 F mutants were associated with clinical resistance to CQ. In Nepal and India, where P. vivax CQR has not been recorded, prevalence of the 976 F mutation is very low (5 %) [ 21 ] or not detected [ 22 ], while in India the presence of the F1076 L mutation was not associated to CQR. In addition, in Madagascar, despite 5 % of clinical failures more than 90 % of Y976 F mutant parasites were detected [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 However there are some threatening reports on chloroquine resistant vivax malaria from different malaria endemic regions of India. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Thus it is becoming a major public health problem that needs to be dealt with on an urgent basis by initiating proper…”
Section: Discussionmentioning
confidence: 99%